Pengaruh inflasi dan BI 7-day reverse repo rate terhadap pembiayaan umkm dengan dana pihak ketiga sebagai variabel intervening - Ramandani, Tita; Arinta, Yusvita Nena (Journal of Economics Research and Policy Studies, 2022)
This study aims to determine the effect of inflation and the BI 7-day reverse repo rate on MSME financing with Third Party Funds as an intervening variable. Data using secondary data were taken from each bank's official websites, Bank Indonesia (BI) and the Central Bureau of Statistics (BPS). The data taken by researchers is from 2015–2020. The method used in the research uses path analysis. The results of this study indicate that inflation and the BI 7-day reverse repo rate do not affect MSME financing. Meanwhile, Third Party Funds have a positive impact on MSME financing. Inflation and the BI 7-day reverse repo rate do not affect Third Party Funds. In addition, third-party funds cannot mediate the effect of inflation or the BI 7-day reverse repo rate on MSME financing.